Sosialisasi Penguatan Strategi Digitalisasi UMKM Berbasis E-Katalog dalam Kemandirian Pangan Desa Trawasan - Nur Khafidhoh; Agus Sifaunajah; Moh. Anshori Aris Widya; Zulfikar Zulfikar (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2026)
The community service program in Trawasan Village aims to empower local food MSMEs in marketing their products through digital platforms. Most MSMEs still rely on conventional promotion, resulting in limited market reach. This program introduces e-catalogues as a promotional medium with a participatory-educational approach through socialization. The results of the activities show an increase in digital literacy, the documentation of products with photos and descriptions, and the availability of a shared platform to expand the market. The activities encourage the use of more familiar platforms, such as WhatsApp Business, as a supporting medium, thereby opening up wider market opportunities for local products.